Impact of Early and Regular Mobilization on Vital Signs and Oxygen Saturation in Patients Undergoing Open-Heart Surgery - Sema Köse; Gülçin Avşar (Brazilian Journal of Cardiovascular Surgery, 2021)
Abstract Introduction: This quasi-experimental study aimed to evaluate the impact of early and regular mobilization on vital signs and oxygen saturation in open-heart surgery patients. Methods: The study universe comprised patients undergoing open-heart surgery in the cardiovascular intensive care unit of a heart center. The study sample consisted of patients who underwent open-heart surgery from November 2016 to April 2017, met the inclusion criteria, and voluntarily agreed to participate in the study. The study included 75 patients. Of these, 67 completed the mobilization program in two days, starting on the first postoperative day. Each patient was mobilized three times: twice on the first postoperative day and once on the second postoperative day. Vital signs and oxygen saturation for each patient were measured 10 minutes before and 20 minutes after each mobilization. Results: The difference between pulse and systolic blood pressure values measured before and after the first mobilization was statistically significant (P<0.05). In addition, the difference between the mean systolic blood pressure values before the first mobilization and after the third mobilization (123.43±14.09 mmHg and 117.94±14.05 mmHg, respectively) was statistically significant (P<0.05). The other parameters measured in relation to the mobilizations were in the normal range. Conclusion: Early and frequent mobilization did not cause vital signs and oxygen saturation to deviate from normal limits in open-heart surgery patients.